E-WOM across digital channels: A comparison of e-commerce and social media impact on consumer purchase intentions - Mohammad Rishad Faridi; Azam Malik; Noor Alam Khan; Asif Iqbal; Sania Khan (Innovative Marketing)
This study analyzed by comparing the effect of e-WOM (electronic word-of-mouth) virtual shopping websites and e-WOM from respondents on social networks on users’ smartphone buying intentions. A research frame is established based on four e-WOM components: e-WOM source credibility, e-WOM source quality, e-WOM source attitude, and e-WOM source format toward the purchase intention of a smartphone. The effect of the independent variables was empirically tested using multiple regression analysis on the dependent variable of customer buying intention. The research was conducted in Uttar Pradesh, a province in India, with 362 respondents administering a questionnaire. Descriptive statistics, ANOVA (analysis of variance), and regression analysis were applied to interpret the source data. The results of regression factors had a strong statistical influence with a probability value of .000 and R2 of .358 according to the outcomes, suggesting that the framework described 35.8 proportion of the variance and that all the factors were major antecedents of buying intention. This study assists digital businesses in determining consumer buying trends through e-WOM on digital platforms. This study proposes a novel concept to understand how e-WOM affects customers’ buying intent from social networks and e-commerce portals. AcknowledgmentThis study is supported via funding from Prince Sattam bin Abdulaziz University project number PSAU/2024/R/1445.